2020
DOI: 10.22463/0122820x.2189
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical characterization of additive manufacturing composite parts

Abstract: Additive Manufacturing is a novel manufacturing method in which the part is produced layer by layer from a 3D CAD model. In this work, we present the mechanical characterization of Fusion Deposition Modeling (FDM). Composite parts made by a nylon matrix with two kinds of fiber reinforcements: carbon fiber or fiberglass. From the obtained microstructure, we perform a division of the composite part in regions, and individual stiffness matrices are encountered by either using a linear elastic isotropic model, for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…As a point of reference, Lupone et al 12 recorded prediction errors ranging from 2.2% to 12.4% for the law of mixtures, 0.9% to 8.3% for the VAS method, and 2.3% to 5.9% for the CLT. León-Becerra et al 44 observed a prediction error of 5.3% when using the VAS method. Based on the acceptable results, these analytical prediction techniques can be used in the 3D printing of long fiber composites to predict mechanical properties for predimensioning and dimensioning purposes.
Figure 15.Comparison of the Young's modulus obtained by analytical prediction methods and tensile test.
…”
Section: Resultsmentioning
confidence: 98%
“…As a point of reference, Lupone et al 12 recorded prediction errors ranging from 2.2% to 12.4% for the law of mixtures, 0.9% to 8.3% for the VAS method, and 2.3% to 5.9% for the CLT. León-Becerra et al 44 observed a prediction error of 5.3% when using the VAS method. Based on the acceptable results, these analytical prediction techniques can be used in the 3D printing of long fiber composites to predict mechanical properties for predimensioning and dimensioning purposes.
Figure 15.Comparison of the Young's modulus obtained by analytical prediction methods and tensile test.
…”
Section: Resultsmentioning
confidence: 98%